2012
DOI: 10.1002/pro.2174
|View full text |Cite
|
Sign up to set email alerts
|

Detection of disordered regions in globular proteins using 13C‐detected NMR

Abstract: Characterization of disordered regions in globular proteins constitutes a significant challenge. Here, we report an approach based on 13 C-detected nuclear magnetic resonance experiments for the identification and assignment of disordered regions in large proteins. Using this method, we demonstrate that disordered fragments can be accurately identified in two homologs of menin, a globular protein with a molecular weight over 50 kDa. Our work provides an efficient way to characterize disordered fragments in glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To define the boundaries of the globular central domain we employed carbon detected NMR experiments to efficiently identify flexible regions. We assigned disordered fragments in BMI1 106-240 by employing a combination of 13 C-detected 2D CACO, CBCACO and CANCO experiments using a previously published protocol39. We identified residues 106–120 and 236–240 as being highly flexible in solution (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To define the boundaries of the globular central domain we employed carbon detected NMR experiments to efficiently identify flexible regions. We assigned disordered fragments in BMI1 106-240 by employing a combination of 13 C-detected 2D CACO, CBCACO and CANCO experiments using a previously published protocol39. We identified residues 106–120 and 236–240 as being highly flexible in solution (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous attempts at structural studies of the BMI1 UBL domain were hampered by protein instability41. To design constructs of BMI1 and PHC2 suitable for structural studies we employed 13 C-detected NMR experiments to identify disordered protein fragments39. Using such an approach we efficiently mapped the minimal folded fragments of BMI1 and PHC2 involved in this interaction highlighting the utility of this methodology in designing constructs for structural biology39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional core units can also be identified experimentally, following limited proteolysis, by mass spectrometry [113]. Finally, experimental methods can be used to identify the disordered regions directly, such as deuterium-hydrogen exchange coupled to mass spectrometry (DXMS) [114–116], or NMR [117]. Unfortunately, many target variants may have to be screened to identify one amenable to crystallization, because in some cases short disordered fragments may even help[118].…”
Section: Target Protein Modification For Enhanced Crystallizabilitymentioning
confidence: 99%
“…The size of the human menin is 615 amino acids, and it varies between different homologs from 539 ( Nematostella vectensis ) to 763 ( Drosophila melanogaster ) amino acids. Bioinformatics analysis and NMR studies revealed that menin is a globular protein with several disordered fragments (Figure 2A) [66]. Truncations of these flexible fragments turned out to be essential for successful crystallization of menin.…”
Section: Structural Studies Of Menin Reveal That Menin Is a “Druggablmentioning
confidence: 99%